Tencent’s Corporate Strategic Organizational Digital Management and Digital Transformation: A case study - Jun, Cui; Cheng, Yan; Ng, Alex, Hou Hong (INTI International University, 2022)
In the recent period, Tencent has changed the current organizational structure. The new person in charge coordinates the company's product, operation, market, and content cooperation in the company's China business, including Wechat, QQ, TIM, Tencent Video, Search, Tencent Games and other businesses and products. Tencent’s corporate strategy upgrade and digital transformation have also begun. As Tencent’s long-time helm, the identity of the founder Ma Hua Teng will be transformed into "Tencent Global CEO". Tencent ‘s corporate strategic transformation is more globalized. CEO of Ma Hua Teng has made it clear that in the future, he will spend more energy to improve the Tencent’s global management team, lead Tencent’s global strategy and digital platform development, and focus more on the exploration and development of long-term major issues. Strategic thinking, including global corporate management research, corporate social responsibility, and new business directions such as education. In addition, Tencent has offices in 30 countries and more than 180 cities, with more than 55,000 employees, and it is expected that the global labor force will reach 10,000 this year. The research in this paper found some literature data from google scholar and Baidu Encyclopedia for analysis and description digital transformation and Strategic Organizational Digital of Tencent, for such a global famous company, global digital management is bound to be a problem.